Utilization of Sealants and Conservative Adhesive Resin Restoration for Caries Prevention by Dental Students - Lakshmi Lakshmanan1 , Vignesh Ravindran2 , Vignesh Ravindran3, EMG Subramanian4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The most prevalent dental caries is a preventable disease and established lesions can become arrested.Traditional restorative treatment has many limitations and there is a need for dentists to manage cariouslesions as far as possible by preventive means. The aim of this study was to investigate the practice of dentalstudents regarding pit and fissure sealants and conservaive adhesive resin restoration for caries prevention.Data was collected from 86000 patients’ dental records in the department of pediatric dentistry to meet theinclusion and exclusion criteria. A total of 5637 records of children who had undergone either pit and fissuresealants or CARR in primary or permanent teeth were evaluated. Descriptive analysis and chi-square testswere performed. Pit and fissure sealants were done in 9637 teeth (882- primary teeth; 8755- permanent teeth)and CARR were done in 328 teeth (178- primary teeth; 150- permanent teeth) with statistically significantdifference (P<0.05). Both sealants and CARR are more prevalent in males (5071-Sealants; 180-CARR) thanin females (4566-Sealants; 148-CARR). Based on the findings of this study, sealant application is the mostcommon treatment done than CARR for caries prevention in both primary and permanent teeth by dentalstudents.